Intravenous Cyclophosphamide Infusion Effects on Skin Fibrosis, IL-6 and TGF-β1 Responses in Systemic Sclerosis with Interstitial Lung Disease - Rakhma Yanti Hellmi; Harry Isbagio; Suharyo Hadisaputro (Indonesian Journal of Rheumatology, 2026)
Background: Systemic sclerosis (SSc) is a chronic multisystem disease characterized by organ fibrosis, microvascular damage, and immunological dysregulation. This study aimed to evaluate the effects of intravenous cyclophosphamide (CYC) infusion on skin fibrosis severity, interleukin-6 (IL-6), and transforming growth factor-beta 1 (TGF-β1) levels in patients with SSc-associated interstitial lung disease (SSc-ILD), compared to conventional disease-modifying antirheumatic drug (DMARD) therapy. Methods: This study included patients meeting the 2013 ACR/EULAR classification criteria for SSc. Thirty-two patients (47.8%) received intravenous CYC, while 35 patients (52.2%) received conventional DMARDs. Skin fibrosis severity, assessed by the modified Rodnan skin score (mRSS), alongside serum IL-6 and TGF-β1 levels, were measured at baseline and after six months of therapy. Efficacy was evaluated by comparing post-treatment values to baseline measurements. Results: Both CYC and conventional DMARDs significantly reduced mRSS and serum TGF-β1 levels post-therapy. When comparing the two groups, the reduction in IL-6 levels demonstrated a trend toward statistical significance (p=0.051). Conclusion: Intravenous CYC therapy substantially reduces skin fibrosis (mRSS) and serum TGF-β1 levels in patients with SSc-ILD.